A Novel Steel Reinforcement Scheme for 3D Printed Concrete Beams: A Study on Shear Behaviour - Khalifa, Mohamed Ashraf (2025)
A Master of Science thesis in Civil Engineering by Mohamed Ashraf Khalifa entitled, “A Novel Steel Reinforcement Scheme for 3D Printed Concrete Beams: A Study on Shear Behaviour”, submitted in June 2025. Thesis advisor is Dr. Adil Tamimi and thesis co-advisor is Dr. Sami Tabsh. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).